The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/00207140600689439
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Views and Attitudes about Hypnosis: A Survey of College Students Across Four Countries

Abstract: The present investigation surveyed attitudes and beliefs about hypnosis across 4 samples of students attending college at the University of New South Wales, Australia; Dortman University, Germany; The Ohio State University, United States; and Shaheed Beheshti University of Medical Sciences, Iran. A total of 280 undergraduate students (70 from each country sampled), ranging in age from 18 to 25 years, completed 3 different questionnaires assessing their opinions and beliefs about hypnosis. Although responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 3 publications
1
47
1
Order By: Relevance
“…In earlier studies (see Green, 2003;Green, Page, Rasekhy, Johnson, & Bernhardt, 2006), the response format was broadened so that responses could range from 1 (not at all true) to 7 (very true), and total scale scores could be calculated. High scores across these four categories of items reflect the belief that hypnosis is an altered state of consciousness, the experience of hypnosis depends on the hypnotist, not the subject, participants experience suggested events in an automatic, involuntary manner, and suggestions are powerful and can't be resisted, respectively.…”
Section: Downloaded By [University Of California Santa Cruz] At 14:45mentioning
confidence: 99%
“…In earlier studies (see Green, 2003;Green, Page, Rasekhy, Johnson, & Bernhardt, 2006), the response format was broadened so that responses could range from 1 (not at all true) to 7 (very true), and total scale scores could be calculated. High scores across these four categories of items reflect the belief that hypnosis is an altered state of consciousness, the experience of hypnosis depends on the hypnotist, not the subject, participants experience suggested events in an automatic, involuntary manner, and suggestions are powerful and can't be resisted, respectively.…”
Section: Downloaded By [University Of California Santa Cruz] At 14:45mentioning
confidence: 99%
“…Australian citizens of Brisbane consider hypnosis to be an altered state of consciousness with memory enhancement qualities (Chant et al, 2006). A survey of cultural views about hypnosis in four different countries also provides information concerning the differences in attitudes about hypnosis in different nations (Green et al, 2006).…”
Section: Myth Of Hypnosismentioning
confidence: 99%
“…Strangely enough, although conceptualizations, practice, and research regarding hypnosis and hypnotherapy have made considerable progress (Naish, 2011;Nash & Barnier, 2008) and although well-known and respected professionals have done a lot to change public opinion on hypnosis, for example, Nash's (2001) article in Scientific American, misinformation and misconceptions are still common (Green, Page, Rasekhy, Johnson, & Bernhardt, 2006;Lynn et al, 2010). In this context, Judith Pintar (2010) stated that at least during the last two centuries the "popular imagination" regarding hypnosis has remained almost unchanged.…”
mentioning
confidence: 97%
“…On the other hand, a survey of college students across four countries conducted by Green, Page, Rasekhy, Johnson, and Bernhardt (2006) returned complex and difficult-to-interpret results. For instance, it reported that, although American students showed the most positive attitude toward hypnosis among the four countries, their OAH scores were not low.…”
mentioning
confidence: 96%